2021
DOI: 10.26497/ao200018
|View full text |Cite
|
Sign up to set email alerts
|

Iodine deficiency in pregnant women on São Miguel Island, Azores. Assessing the Impact of Corrective Measures

Abstract: Introdução: O iodo é um oligoelemento essencial que tem como função primordial no organismo a síntese das hormonas da tiróide, as quais desempenham um papel determinante no crescimento e desenvolvimento, especialmente na maturação do sistema nervoso. Em 2012, um trabalho do Grupo de Estudos da Tiróide da Sociedade Portuguesa de Endocrinologia Diabetes e Metabolismo observou nas grávidas açorianas, uma mediana das iodúrias de 46,2 μg/L. Das mulheres, 98,6% apresentavam iodúrias insuficientes (<150 μg/L) e 55,7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It is also displayed the importance of health care workers as a trusted source of information about IS consumption and iodine deficiency (13,14,22,23). Even though the use of MSCI and PBIS was sparse in this study, the efforts put in action by the government are already showing an important improvement in pregnant and breastfeeding women, to whom the PBIS is readily prescribed and freely provided (10). Increasing informed decision making and providing awareness on the benefits of PBIS might provide even further improve results in pregnant women (24).…”
Section: Discussion Of the Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…It is also displayed the importance of health care workers as a trusted source of information about IS consumption and iodine deficiency (13,14,22,23). Even though the use of MSCI and PBIS was sparse in this study, the efforts put in action by the government are already showing an important improvement in pregnant and breastfeeding women, to whom the PBIS is readily prescribed and freely provided (10). Increasing informed decision making and providing awareness on the benefits of PBIS might provide even further improve results in pregnant women (24).…”
Section: Discussion Of the Resultsmentioning
confidence: 81%
“…In a 2020 study conducted in São Miguel Island, Azores, it was observed a significant reduction in iodine deficiency in schoolchildren and pregnant women. Some of these results were attributed to the implementation of IS in Azorean houses and canteens of all public schools (10,11). These efforts were directed at all Azorean population, including Faial Island's population, and its effectiveness has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the most recent data suggest that despite women’s adherence to the iodine supplementation recommendation, pregnant women are still iodine-insufficient [ 26 , 27 ]. As for children, a recent study points to iodine sufficiency (median urinary iodine concentration of 129 μg/L), even though 32% of children were still found with urinary iodine levels considered insufficient.…”
Section: Introductionmentioning
confidence: 99%